AGENS HAYATI SEBAGAI ALTERNATIF PENGENDALIAN KARAT PUTIH (Puccinia horiana) PADA KRISAN - Febry Nurhidayati; Desy Setyaningrum; Didik Suryadi; Cahyaningtyas Putri Suhita; Dewi Nawang Suprihatin; Anditya Gilang Rizky P; Hardian Ningsih; Dimar Hantari; Edi Paryanto; Zainal Arifin (Fakultas Pertanian Universitas Janabadra, 2026)
Chrysanthemum (Chrysanthemum spp.) is an important floricultural commodity in Indonesia. However, its production is seriously threatened by white rust caused by Puccinia horiana. Conventional control still depends on synthetic fungicides, which pose risks of pathogen resistance and environmental contamination. The use of biological control agents (BCAs) offers an environmentally friendly and sustainable alternative within the framework of Integrated Pest Management (IPM). This review summarizes current studies on the use of Pseudomonas fluorescens, Bacillus subtilis, Trichoderma spp., and Cladosporium spp. for managing white rust in chrysanthemum. The main mechanisms include antibiosis, parasitism, competition for space and nutrients, and induced systemic resistance (ISR). Research shows that BCAs can suppress P. horiana infection and improve plant growth, although their effectiveness varies depending on environmental conditions, formulation stability, and farmer adoption. Future research should focus on locally adapted isolates, improved formulation technology, and multilocation trials to ensure field consistency. Policy support and farmer participation are also essential to expand the use of BCAs and promote sustainable chrysanthemum production.